Dynamic Eccentricity Modeling of a Switched Reluctance Motor - LORENCKI, Jakub; CHMIELEWSKI, Adrian (Engineering Transactions, 2025)
The switched reluctance motor (SRM), known for its robust and simple construction, is widely utilized in critical applications. This study investigates the impact of rotor dynamic eccentricity on the motor's current signal. Our research introduces a straightforward diagnostic method to detect and quantify dynamic eccentricity by analyzing the current signal spectrum. This approach specifically focuses on identifying amplitude increases in characteristic additional harmonics, leveraging fundamental electromagnetic transformations to eliminate the need for complex algorithms. Through coupled computer simulations, combining a finite element analysis model (FEMM) with dynamic equation solutions in Simulink, this study identifies specific eccentricity ranges and their corresponding characteristic current values, offering a reliable tool for SRM condition monitoring.